2020
DOI: 10.3758/s13423-019-01668-9
|View full text |Cite
|
Sign up to set email alerts
|

Conflict monitoring and the affective-signaling hypothesis—An integrative review

Abstract: Conflict-monitoring theory proposes that conflict between incompatible responses is registered by a dedicated monitoring system, and that this conflict signal triggers changes of attentional filters and adapts control processes according to the current task demands. Extending the conflict-monitoring theory, it has been suggested that conflict elicits a negative affective reaction, and that it is this affective signal that is monitored and then triggers control adaptation. This review article summarizes researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
133
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(160 citation statements)
references
References 254 publications
(264 reference statements)
21
133
4
2
Order By: Relevance
“…domain-general avoidance learning). Still, our finding does lend credence to the idea that that cognitive control can be understood as an emotional process (Inzlicht et al, 2015), and that conflict can be registered as an aversive event (i.e., Botvinick, 2007;Dignath et al, 2020;Dreisbach & Fischer, 2015), at least in the dACC/pre-SMA. Similarly, additional analyses further show that our effect is unlikely to be driven by general differences in reaction time or task difficulty, or differences in arousal.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…domain-general avoidance learning). Still, our finding does lend credence to the idea that that cognitive control can be understood as an emotional process (Inzlicht et al, 2015), and that conflict can be registered as an aversive event (i.e., Botvinick, 2007;Dignath et al, 2020;Dreisbach & Fischer, 2015), at least in the dACC/pre-SMA. Similarly, additional analyses further show that our effect is unlikely to be driven by general differences in reaction time or task difficulty, or differences in arousal.…”
Section: Discussionsupporting
confidence: 72%
“…In other words, the dACC is thought to register "cognitive" conflict as an aversive event. In accordance with this idea, recent studies have supported the presence of a behavioral bias to avoid conflict, and have also shown that humans automatically evaluate conflict as negative (Dignath et al, 2020;Dreisbach & Fischer, 2015;Inzlicht et al, 2015).…”
Section: Introductionmentioning
confidence: 61%
“…The relative higher cognitive load may have led to more monitoring for the expected conflict trials and thus more slowing. Assuming an involvement of an affective component in conflict and error monitoring, the higher cognitive load may elicit a stronger affective response in children leading to stronger slowing [53,54]. On the other hand, less developed performance adjustment skills would lead to stronger after-effects of responding (correctly or incorrectly) to a conflict trial [55].…”
Section: Plos Onementioning
confidence: 99%
“…Alternatively, following previous work on affective priming and conflict (Dignath, Eder, Steinhauser, & Kiesel, 2020;Fritz & Dreisbach, 2013), adjectives could act as affective primes (Bush et al, 2018). Although we cannot completely rule out this possibility, previous results suggest otherwise.…”
Section: Discussionmentioning
confidence: 76%